Performing soccer-specific training with blood flow restriction enhances physical capacities in youth soccer players - Hosseini Kahak, S. A.; Kianigul, M.; Haghighi, A. H.; Nooghabi, M. J.; Scott, B. R. (The Journal of Strength and Conditioning Research, 2022)
This study investigated the effect of soccer training with blood flow restriction (BFR) on physical performance in youth athletes. Nineteen semiprofessional soccer players were randomly assigned to either normal soccer training (ST; n = 9) or soccer training with BFR (STBFR; n = 10). Both groups performed identical activities during a 6-week preseason training phase, either with or without lower limb BFR. Training included soccer-specific drills, small-sided games, plyometrics, and continuous running. Before and after the intervention, players were assessed for leg extension strength and endurance, countermovement jump performance, 40-yd sprint time, change-of-direction (COD) ability, aerobic endurance, and soccer-specific endurance (while dribbling a ball). Significantly larger improvements were observed in the STBFR compared with the ST group for tests of muscular endurance (74.8 ± 34.1% vs. 4.0 ± 14.6%), COD (8.1 ± 3.7% vs. 2.8 ± 4.7%), and aerobic (54.1 ± 19.6% vs. 24.7 ± 27.2%) and soccer-specific endurance (58.4 ± 19.6% vs. 22.7 ± 10.2%). Main effects for time were observed for maximal strength, jumping, and sprinting performance (p < 0.001) but with no group and time interaction. These findings demonstrate that team sport training with BFR can enhance physical qualities that are related to performance in youth soccer players. This application of BFR may improve the adaptive responses of muscles, without having to dedicate additional training time to muscular qualities.